Pathways to Conspiracy Theorizing on YouTube in Japan - Ota, Koki; Chujyo, Masaki; Toriumi, Fujio (Proceedings of the International AAAI Conference on Web and Social Media, 2025)
This study investigates how viewers and creators on Japanese YouTube channels progress towards conspiracy theories. By categorizing channels based on ideological or financial motives and analyzing engagement metrics such as views, likes, and comments, we find that channels driven by monetization, particularly Monetized Conspiracists, promote conspiracy theories more vigorously. This indicates that financial incentives are a crucial factor in the proliferation of such content. Channels that package conspiracy theories in formats like entertainment or spirituality serve as gateways, facilitating viewers’ progression towards more extreme conspiracy-laden content. Understanding these pathways is vital for crafting strategies to counteract the spread of conspiracy theories on social media.